Combined effects of rice husk ash and hybrid fibres on the fresh and mechanical properties of recycled aggregate concrete. (2022) - Aminu Alhaji, Musa; Kumar Sharma, Pushpendra
Abstract: Enhancing the fresh and mechanical behaviours of recycled aggregate concrete (RAC) to be comparable to normal concrete is critical. Therefore, this study aimed to examine recycled aggregate concrete's fresh-state and mechanical behaviours by partially substituting cement with rice husk ash (RHA) and incorporating a hybrid of steel and glass fibres. The recycled coarse aggregate was systemically used to the constant percentage of 75% to replace natural coarse aggregate, and rice husk ash was utilized by 10%, 15% and 20% as cement substitutes. The hybrid of glass fibres (GF) and steel fibres (XSF) was added by percentage proportions of 0.5 %GF-0.5 %XSF, 0.25 %GF-0.75 %XSF and 0.75 %GF-0.25 %XSF. The total fibres volume fraction was taken as 1.0%. Fresh properties were investigated using slump, setting times, consistency tests, while mechanical parameters were also evaluated by testing the compressive and flexural behaviours. The results from the experiment revealed that substitution of cement with rice husk ash affects the workability behaviour of fresh concrete mixes, but by adding superplasticizer in the mix the loss in workability was compensated. Additionally, incorporation of fibres and rice husk ash improves the mechanical behaviours of RAC in comparison to normal concrete. The result further revealed that the combination of 75% recycled coarse aggregate, 15% cement replacement with rice husk ash, and 0.5% glass fibre-0.5% steel fibre can be considered as optimum percentage combinations in achieving desirable mechanical performance of RAC. Therefore, the study concluded that this combination can be used for structural purposes.